Perbandingan Hutang terhadap Ekuitas, Arus Kas Operasi, dan Nilai Perusahaan Konstruksi - Annisa, Mutiara Lusiana; Amalia, Rizki Fitri (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: The aim of this research is to analyze the influence of the debt-to-equity ratio (DER) and operating cash flow on company value. Methodology: This study examines the impact of debt-to-equity ratio and operating cash flow (OCF) on firm value, using data from 15 IDX-listed construction companies during 2022–2023. Companies were selected through purposive sampling, based on their financial report completeness and continuous listing. Data were sourced from documentation and the IDX website and analyzed using statistical methods, including multiple regression. Result: The study finds that the inefficient use of OCF significantly reduces firm value, as high operational costs without matching revenue lower investor confidence. Conclusions: This study shows that a high debt-to-equity ratio and inefficient use of Operating Cash Flow negatively affect the IDX value of construction companies. High debt increases financial risk, while poor cash flow management reduces investor confidence, both of which lead to lower firm value. Limitations: This study is limited by the availability and consistency of financial report data, as not all companies may have complete records for the period 2022–2023. Additionally, the short research timeframe may not fully reflect the long-term patterns or trends that could influence the relationship between operating cash flow, capital structure, and firm value. Contribution: This study adds to financial theory by exploring the relationship between operating cash flow, capital structure, and firm value, and offers practical insights for construction company managers in planning effective funding strategies.